2020
DOI: 10.1002/tox.22894
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Microcystis aeruginosa cells lysate containing microcystins on physiological and molecular responses in the nematode Caenorhabditis elegans

Abstract: Microcystins (MCs) are potent toxins produced by environmental cyanobacterial blooms. The present study evaluated the effects of a Microcystis aeruginosa cyanobacterial lysate containing 0.1, 1, and 10 μg L−1 MC‐LR equivalent in the C. elegans Bristol N2 wild‐type and the effects caused by equivalent concentrations of a MC‐LR standard. The lysate was prepared from a culture of toxic strain (RST9501) originated from the Patos Lagoon Estuary (RS, Brazil). The minimal concentration necessary to cause significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The free‐living nematode Caenorhabditis elegans , as a model organism, has been applied to environmental biomonitoring 4 . The toxicity of environmental contaminants can be evaluated by testing the worm's lethality, behavior, growth, reproduction, feeding, gene expression and so on in the biomonitoring 4–12 . Transgenic strains of C. elegans , such as hsp16::gfp and mtl‐2::gfp , have been developed and applied in environmental toxicology 2,13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…The free‐living nematode Caenorhabditis elegans , as a model organism, has been applied to environmental biomonitoring 4 . The toxicity of environmental contaminants can be evaluated by testing the worm's lethality, behavior, growth, reproduction, feeding, gene expression and so on in the biomonitoring 4–12 . Transgenic strains of C. elegans , such as hsp16::gfp and mtl‐2::gfp , have been developed and applied in environmental toxicology 2,13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Caenorhabditis elegans , as a model organism, has been used extensively in ecotoxicological research due to its short lifespan, easy cultivation, and sequenced genome 11 . In addition, C. elegans has various genes that are highly sensitive to and inducible by pollutants 12,13 . Leelaja and Rajini 14 reported that monocrotophos at sublethal doses induced significant damage to C. elegans , resulting in a decrease in glutathione (GSH) content and superoxide dismutase (SOD) activity.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, C. elegans has various genes that are highly sensitive to and inducible by pollutants. 12,13 Leelaja and Rajini 14 reported that monocrotophos at sublethal doses induced significant damage to C. elegans, resulting in a decrease in glutathione (GSH) content and superoxide dismutase (SOD) activity. In a previous study, exposure to glyphosate led to mitochondrial inhibition and hydrogen peroxide accumulation in the nematodes.…”
mentioning
confidence: 99%